Quantitative assessment of microenvironment characteristics and metabolic activity in glioma via multiphoton microscopy. Issue 10 (17th July 2019) - Fang, Na; Wu, Zanyi; Wang, Xingfu; Lin, Yuanxiang; Li, Lianhuang; Huang, Zufang; Chen, Yupeng; Zheng, Xianying; Cai, Shanshan; Tu, Haohua; Kang, Dezhi; Chen, Jianxin
Abstract: Tumor microenvironment and metabolic activity in gliomas are the important biomarkers to evaluate the progression of gliomas. Many evidences have suggested that the targeting of metabolic activity and tumor microenvironment simultaneously can be more effective to take the tumor therapy. Therefore, the noninvasive, accurate assessment of tumor microenvironment and metabolic activity is quite important in clinical practice. Multiphoton microscopy (MPM), based on two‐photon‐excited fluorescence and second harmonic generation was performed on unstained glioma tissues. With our combined image analysis approaches, our research findings indicate that MPM is able to qualitatively and quantitatively describe the microenvironment characteristics in gliomas, such as collage deposition in extracellular matrix, lymphocyte infiltration and tumor angiogenesis, etc. Meanwhile, the metabolic activity can also be quantitatively evaluated by optical redox ratio, NADH and FAD intensity. With the microendoscope and fiberscope are portable, MPM technique can be used to perform in‐vivo studies and clinical examinations in gliomas. Abstract : Multiphoton microscopy (MPM) combined with customized image processing algorithms is taken as a quick and label‐free tool to describe microenvironment characteristics and metabolic activity in glioma. This approach allows the MPM to directly visualize and automatically assess microenvironment characteristics and metabolic activity in the unstained glioma tissues. It offers a fundamental proof of reasoning to put the in‐vivo fiberscopes and multiphoton microendoscopes into clinical use.